Development of Low Cost Dust Collector for Textile Industry - Prof. Sumit S. Dharmarao; Ravindra B. Bantanur; Abu-RehanJ. Bedrekar (International Journal of Innovations in Engineering Research and Technology, 2021)
Cotton dust in the work place is major problem in cotton textile industries. This problem is more severe in spinning section. Dust consists of small and microscopic particles of various substances which are present as suspended particles in air. These particles are harmful to human health. Because of this various diseases are occurred like shortness of breath, cough, and lungs cancer. Variousaspects of health hazards in textile industries have been discussed and measure hazards is lungs cancer to reduce this health hazards is lungs cancer our dust collector is helpful.